Student Exchange Alumni of Merdeka Belajar Kampus Merdeka (MBKM) Program Shared Voice for English Education Department Improvement at STKIP Yapis Dompu - Ismail (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
There have been studies exploring the implementation of student exchange of MBKM program. However empirical study which investigates Shared Voice of student exchange alumni of Merdeka Belajar Kampus Merdeka (MBKM) Program is uncommon. This study relies on semi-structured interview data from 6 English Education students who participated in student exchange program batch II and III of Merdeka Belajar Kampus Merdeka (MBKM) Program held by the Indonesian Ministry of Education, Culture, Research, and Technology. This study aims to explore student exchange alumni’s suggestion for English education department improvement. The data were analyzed using thematic analysis adapted from (Braun & Clarke, 2006) which consists of 6 steps. As a result of studying at other Indonesian universities, they highly recommend story-telling, TOEFL, and microteaching courses to be compulsory courses in English Education Department of STKIP Yapis Dompu. Other main finding in this research is that Lecturers should be more assertive in providing teaching treatment to students to promote students discipline and motivation in doing assignments. The last finding is that lecturers of English Education Department of STKIP Yapis Dompu are highly recommended to adapt game-based learning using technology to gain effective, fun, and interactive learning